OPTIMALISASI HASIL BELAJAR MELALUI INTEGRASI KECERDASAN BUATAN DALAM PEMBELAJARAN ADAPTIF PADA MATA KULIAH PROFESI PENDIDIKAN - Alim, Bahrul; Khusnah, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to optimize learning outcomes through the integration of artificial intelligence in adaptive learning for the Professional Education course. A mixed methods sequential explanatory design was employed with 160 students from the Physical Education, Health and Recreation Study Program at Universitas Negeri Makassar, divided into experimental (n=80) and control groups (n=80). The experimental group utilized AI-integrated adaptive learning systems (ChatGPT Plus, Perplexity AI, and Claude), while the control group used conventional learning methods. Data were collected through learning achievement tests and in-depth interviews. Results showed a significant difference in posttest scores between groups (t=7.893; p<0.001), with the experimental group achieving a mean gain score of 19.3 points compared to 11.1 points in the control group. Qualitative findings revealed that AI integration enhanced learning motivation, facilitated access to information, and enabled learning personalization. However, technical challenges and ethical concerns regarding academic integrity were identified. This study concludes that strategic AI integration in adaptive learning significantly improves learning outcomes in Professional Education courses while requiring careful consideration of pedagogical, technical, and ethical aspects.